Integration Of Moral Curriculum With Arabic Literature Stories And Parables Of The Qur'an Qsp - Kirembwe Rashid Abdul Hamed; Mohd Aderi bin Che Noh; Siti Rosilawati binti Ramlan; Sakinah binti Ahmad; Hayati binti Ismail; Maziahtusima Binti Ishak (KEMENTERIAN AGAMA REPUBLIK INDONESIA UNIVERSITAS, 2025)
Indexed by WOS